Neutrophils Are Not Less Sensitive Than Other Blood Leukocytes to the Genomic Effects of Glucocorticoids - Hirsch, Gaelle; Lavoie-Lamoureux, Anouk; Beauchamp, Guy; Lavoie, Jean-Pierre (PLOS ONE, 2012)
Background Neutrophils are generally considered less responsive to glucocorticoids compared to other inflammatory cells. The reported increase in human neutrophil survival mediated by these drugs partly supports this assertion. However, it was recently shown that dexamethasone exerts potent anti-inflammatory effects in equine peripheral blood neutrophils. Few comparative studies of glucocorticoid effects in neutrophils and other leukocytes have been reported and a relative insensitivity of neutrophils to these drugs could not be ruled out. Objective We assessed glucocorticoid-responsiveness in equine and human peripheral blood neutrophils and neutrophil-depleted leukocytes. Methods Blood neutrophils and neutrophil-depleted leukocytes were isolated from 6 healthy horses and 4 human healthy subjects. Cells were incubated for 5 h with or without LPS (100 ng/mL) alone or combined with hydrocortisone, prednisolone or dexamethasone (10−8 M and 10−6 M). IL-1β, TNF-α, IL-8, glutamine synthetase and GR-α mRNA expression was quantified by qPCR. Equine neutrophils were also incubated for 20 h with or without the three glucocorticoids and cell survival was assessed by flow cytometry and light microscopy on cytospin preparations. Results We found that glucocorticoids down-regulated LPS-induced pro-inflammatory mRNA expression in both cell populations and species. These drugs also significantly increased glutamine synthetase gene expression in both equine cell populations. The magnitude of glucocorticoid response between cell populations was generally similar in both species. We also showed that dexamethasone had a comparable inhibitory effect on pro-inflammatory gene expression in both human and equine neutrophils. As reported in other species, glucocorticoids significantly increase the survival in equine neutrophils. Conclusions Glucocorticoids exert genomic effects of similar magnitude on neutrophils and on other blood leukocytes. We speculate that the poor response to glucocorticoids observed in some chronic neutrophilic diseases such as severe asthma or COPD is not explained by a relative lack of inhibition of these drugs on pro-inflammatory cytokines expression in neutrophils.